Hyperglycemia-associated Alzheimer’s-like symptoms and other behavioral effects attenuated by Plumeria obtusa L. Extract in alloxan-induced diabetic rats - Naz, Sumeera; Imran, Imran; Farooq, Muhammad Asad; Shah, Syed Adil Hussain; Ajmal, Iqra; Zahra, Zartash; Aslam, Aqsa; Sarwar, Muhammad Irfan; Shah, Jaffer; Aleem, Ambreen (Frontiers in Pharmacology, 2022)
Diabetes mellitus is a chronic metabolic complaint with numerous short- and long-term complications resulting in harm to the person’s physical and psychological health. Plumeria obtusa L. has traditional claims to treat diabetes and improve its complications related to behavior. Plumeria is a genus with antipsychotic activities. This study's objective was to examine the effects of a methanolic extract of Plumeria obtusa L. on the attenuation of diabetes, associated Alzheimer and behavioral effects. A single dosage of alloxan was administered to the experimental groups to develop diabetes (150 mg/kg, intraperitoneal) and, rats were administered with selected doses of methanolic extract of Plumeria obtusa L. (Po.Cr) and glibenclamide, 0.6 mg/kg for 45 consecutive days and behavioral effects were evaluated by three validated models of anxiety viz., while the antidepressant effect was evaluated by forced swimming test (FST) and memory and learning were estimated by the morris water maze (MWM) task. Po. Cr was also evaluated for phytochemicals using TPC, TFC, and HPLC, as well as anti-oxidant capability utilizing DPPH radical scavenging test, total oxidation capacity, and total reducing capacity. In alloxan induced model of diabetes, the administration of Po.Cr and glibenclamide for 45 days produce a marked decrease (p<0.001) in hyperglycemia. Po.Cr also showed advancement in indicators such as weight of the body and lipid profile (p<0.05) and restores the liver functioning enzyme (ALT) levels (p<0.001). Diabetic rats presented more Alzheimer-like symptoms with lessened memory and learning, anxiety and depression in comparison to non-diabetic normal rats, while treated diabetic rats have shown significant improvements in such memory and behavioral effects. The outcomes demonstrate that Po.Cr reversed the alloxan-induced hyperglycemia and ameliorate Alzheimer and behavior which encourages the conventional use of the plant to treat diabetes and complications.